Preparation of Metal-Containing Diamond-Like Carbon Films by Magnetron Sputtering and Plasma Source Ion Implantation and Their Properties - Stefan Flege; Ruriko Hatada; Andreas Hanauer; Wolfgang Ensinger; Takao Morimura; Koumei Baba (Advances in Materials Science and Engineering)
Metal-containing diamond-like carbon (Me-DLC) films were prepared by a combination of plasma source ion implantation (PSII) and reactive magnetron sputtering. Two metals were used that differ in their tendency to form carbide and possess a different sputter yield, that is, Cu with a relatively high sputter yield and Ti with a comparatively low one. The DLC film preparation was based on the hydrocarbon gas ethylene (C2H4). The preparation technique is described and the parameters influencing the metal content within the film are discussed. Film properties that are changed by the metal addition, such as structure, electrical resistivity, and friction coefficient, were evaluated and compared with those of pure DLC films as well as with literature values for Me-DLC films prepared with a different hydrocarbon gas or containing other metals.